Clinical Insight into aortic arch and brachiocephalic trunk variations among fetuses of different gestational ages (International Journal of Scientific Research and Management (IJSRM), 2017)
This study provides quantitative data and information about the variations in branching patterns of aortic arch, normal lengths of BT and trachea, as well as their diameters, in 30 spontaneously aborted human foetuses aged 14– 35 weeks. Among all the foetuses examined, the aortic arches were found to have mainly two kind of variations in its branching pattern, without gender differences. In 53% of cases, the usual pattern of the aortic arch with its three main branches was observed. A common origin of the brachiocephalic trunk and left common carotid artery occurred in 35% of individuals. However, in 12% of the cases, common origin of all the three branches arising from aortic arch was observed No significant gender differences were observed (p ≥ 0.05). Length of brachiocephalic trunk was observed to vary from 4.39 mm to 10.79 mm. Diameter of brachiocephalic trunk was observed to be 2.58 ± 0.79 mm at its point of origin. Increase in length of the brachiocephalic trunk was marked between 16 and 16.5 weeks, and last peak was seen after 27 weeks. Both length and diameter of trachea showed significant increase at 16weeks and 27 weeks. We also observed level at which trachea was being crossed by BT. In 65% cases, BT was seen crossing trachea at level of lower one third during its course from origin to its division, while it was seen crossing trachea at its middle in rest of the cases. Such high rate of variations in branching pattern among fetuses can be attributed to their developmental. The variant branches that arise from the aortic arch are due to the changes in the extent of the fusion process and absorption of some of the aortic arch into aortic sac. These variations represent an important morphological risk factor for arterial occlusion and difficulty in catheterization